Análise da concordância nominal na fala de Vitória/ES : o linguístico, o social e o estilístico - Scardua, Juliana Rangel (2018)
This study analyzes the variation of the number agreement among the elements of the noun phrase in the speech of Vitória, capital of Espírito Santo. The data of this research were taken from the “Projeto Português Falado na Cidade de Vitória” (PortVix), comprising 46 interviews stratified by sex/gender, age group and schooling of speakers (YACOVENCO, 2002; YACOVENCO et al., 2012). Based on the theory and methods of Variationist Sociolinguistics (LABOV, 2008 [1972]), we aim to highlight the strongly well-ordered system that governs noun phrase agreement. For the quantitative analysis, we used the Goldvarb X program (SANKOFF; TAGLIAMONTE; SMITH 2005), which selected as statistically significant all the controlled linguistic and social variables, including the stylistics one. Our results reveal a plural marking rate in capixaba speech in the order of 88.6%, since from the total of 10.923 data, 9.683 are agreement cases. The linguistic variables show that the leftmost nominal elements in the noun phrase, the most prominent ones and those preceded by more marks are the ones that have the greatest chance of retaining the plural morpheme. The social variables indicate that males, younger age groups and speakers with higher level of education are the ones that mark more the plural in Vitória. The stylistic variable, investigated using of the Decision Tree method (LABOV, 2001a) and after being remodeled, indicates usually more agreement in the careful speech and less in casual speech. Furthermore, it suggests that the more educated speakers make sharper stylistic changes due to attention to speech than the less educated ones. Therefore, in addition to collaborating with the linguistic studies of Espírito Santo demonstrating how the capixaba variety aligns or distances itself from other Brazilian varieties, our work contributes to the understanding of the role of style in linguistic variation in general.